Relics of the Oral Tradition of the Artsakh-Armenians Emigrated to Pyatigorsk - Svazlian, Verjiné (ՀՀ ԳԱԱ)
In the summer of 1964, the Institute of Archaeology and Ethnography of the Academy of Sciences of Armenia had sent me on an academic mission to the town of Pyatigorsk in the territory of Stavropol, Russia to study the lifestyle and folklore of the Armenian ethnic group living there. When I arrived at Pyatigorsk, I was informed that Armenians emigrated from Karabakh (Artsakh) were living in a separate district. In those years Karabakh was inaccessible for the armenologist-intellectuals. The Azeri authorities did not allow the Armenian archaeologists to go there and make excavations, inasmuch as they were terrified from the fact that they would bring to light numerous and irrefutable proofs testifying that that marvelous territory, bestowed on them in 1921, was of a native Armenian origin. But for me, as a folklorist-ethnographer, it was interesting to know when and whence they had migrated to Pyatigorsk, what changes they had undergone under the conditions of coexistence with the native people, whether they remained sincere to the traditions of their cradle, etc.
Keywords: Հայագիտություն; Հայոց պատմություն; Պատմություն; Հայոց ցեղասպանություն (1915); Հայագիտական ժառանգություն; Հնագիտություն և ազգագրություն; Փիլիսոփայություն և իրավունք; Արվեստ և ճարտարապետություն; Ժողովրդագրություն և կառավարում